2014
DOI: 10.2807/1560-7917.es2014.19.15.20772
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic clinical samples and environmental sampling for enterovirus and parechovirus surveillance in Scotland, 2010 to 2012

Abstract: Human enteroviruses (EV) and parechoviruses (HPeV) within the family Picornaviridae are the most common causes of viral central nervous system (CNS)associated infections including meningitis and neonatal sepsis-like disease. The frequencies of EV and HPeV types identified in clinical specimens collected in Scotland over an eight-year period were compared to those identified in sewage surveillance established in Edinburgh. Of the 35 different EV types belonging to four EV species (A to D) and the four HPeV type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 23 publications
13
59
0
Order By: Relevance
“…The EEVS in the Bible Belt and Ter Apel show a high diversity of NPEV types in the sewage, similar to previous reports about sewage waters (22). In the Bible Belt and Ter Apel surveillance EV-B strains prevailed, and in the Ter Apel sewage EV-C viruses were detected relatively frequently.…”
Section: Discussionsupporting
confidence: 74%
“…The EEVS in the Bible Belt and Ter Apel show a high diversity of NPEV types in the sewage, similar to previous reports about sewage waters (22). In the Bible Belt and Ter Apel surveillance EV-B strains prevailed, and in the Ter Apel sewage EV-C viruses were detected relatively frequently.…”
Section: Discussionsupporting
confidence: 74%
“…Contrary to our study, in which fecal specimens were collected from healthy individuals, clinical samples analyzed in the above-referenced studies were obtained from patients with enterovirus-compatible disease. A wider introduction of molecular methods of enterovirus typing could provide more accurate information on circulating enteroviruses, as Harvala et al indicated (30). Implementation of molecular methods for EV screening could be beneficial in terms of increased sensitivity of detection and speed with which results can be reported, as well as reduced workload and total cost due to the exclusion of EV-negative samples from further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…High detection frequencies (41-78z) and high nucleotide sequence diversity of HPeVs in wastewater samples suggest that analysis of wastewater is a practical approach to detection and research on this virus (13,14). In contrast, lower detection frequencies (2.2-7.4z) have been reported for the stool samples collected from patients with suspected viral infections (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental surveillance, either alone or with clinical analyses, has been conducted to better understand the epidemiology of HPeV infections (13,14). High detection frequencies (41-78z) and high nucleotide sequence diversity of HPeVs in wastewater samples suggest that analysis of wastewater is a practical approach to detection and research on this virus (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation